Proposed Marketing Strategy To Enhance The Competitiveness In A Mixue Franchisee Store (Case Study: Mixue Merdeka Lhokseumawe) - Anggi Nur Fadhila (Green Publisher Indonesia, 2025)
This research aimed to develop a competitive marketing strategy for Mixue Merdeka Lhokseumawe, a franchise in Aceh, within a saturated food and beverage market. Despite the Mixue brand's strengths in affordability and quality, the Lhokseumawe outlet faced underperformance, with sales and ROI below expectations. Analysis revealed competitive pressure from local rivals and limitations imposed by the franchisor, such as restrictions on pricing and product innovation. The study focused on two key objectives: assessing internal and external conditions and formulating a tailored marketing strategy. A qualitative approach was used, including interviews with stakeholders and consumers, alongside quantitative methods for segmentation. Strategic analysis employed frameworks like VRIO, PESTEL, and Porter’s Five Forces, leading to SWOT identification and TOWS matrix development. Findings indicated that Mixue Merdeka possesses strengths like experienced management and high customer satisfaction but faces challenges such as limited pricing autonomy and intense competition. Strategic directions emphasized market penetration and product modification, utilizing the 8Ps marketing mix. Key strategies included maintaining product consistency, smart pricing, enhancing store location appeal, and leveraging social media for promotions. The comprehensive strategy aims to build competitive advantage despite franchise limitations, providing a roadmap for leveraging resources effectively. Future research is suggested to assess the long-term impacts of these strategies on customer loyalty and ROI.